Piper Crocatum Ruiz and Pav as A Commonly Used Typically Medicinal Plant From Indonesia: What Do We Actually Know About It? Scoping Review - Setyawati, Andina; Wahyuningsih, Mae Sri Hartati; Nugrahaningsih, Dwi Aris Agung; Effendy, Christantie; Ibeneme, Sam (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Aims: Piper crocatum Ruiz & Pav (P. crocatum) has been widely used medicinally among ethnic communities in Indonesia to treat a variety of diseases through various preparation- application techniques, duration, and frequency of use. Since research on the benefits of P. crocatum is still limited, our scoping review aimed to identify the key findings resulting from experimental studies regarding the medicinal uses of P. crocatum. Methods: We conducted a scoping review using the framework developed by Arksey and O’Malley. Databases were searched using CAB Direct, ProQuest, ScienceDirect, SpringerLink, and Google Scholar. Data were extracted and tabulated using Microsoft Office Excel 2013. Results: Sixteen articles fulfilled were included in the scoping review. Three key concepts were emerged from this scoping review: 1) Study characteristics indicated the most prevalent type of research was in vivo experiment (n=14) with the highest number of preparations using ethanol extracts (n=8) and P. crocatum sample were mostly sourced from Indonesia (n=9); 2) Seventeen screened metabolites were reported and the most frequently identified were steroids and flavonoids, followed by polyphenols and saponins; and 3) Eight potential activities of P. crocatum were reported as follows: anti-inflammatory, pro-wound healing, antibacterial, antioxidant, anti-necrotic, antitumoral, hepatoprotective, and anti-hyperglycaemic. Conclusion: P. crocatum has various metabolites that might influence the reported potential therapeutic activities with different preparation-application techniques, uses, and duration, yet the scientific evidence conducted in clinical study is still limited. Future research needs to perform testing standardized preparations of P. crocatum to be developed as novel therapeutic agents in wounds, infective diseases, cancers, diabetes, and liver diseases.